A Descriptive Analysis of Outpatient Antimicrobial Use for Urinary Tract Infections in Virginia. (October 2020) - Mazdeyasna, Hasti; Bernard, Shaina; Kang, Le; Godbout, Emily; Lee, Kimberly; Pakyz, Amy; Noda, Andrew; Kim, Jihye; Markley, John Daniel; Doll, Michelle Elizabeth; Bearman, Gonzalo
Abstract : Background: Data regarding outpatient antibiotic prescribing for urinary tract infections (UTIs) are limited, and they have never been formally summarized in Virginia. Objective: We describe outpatient antibiotic prescribing trends for UTIs based on gender, age, geographic region, insurance payer and International Classification of Disease, Tenth Revision (ICD-10) codes in Virginia. Methods: We used the Virginia All-Payer Claims Database (APCD), administered by Virginia Health Information (VHI), which holds data for Medicare, Medicaid, and private insurance. The study cohort included Virginia residents who had a primary diagnosis of UTI, had an antibiotic claim 0–3 days after the date of the diagnosis and who were seen in an outpatient facility in Virginia between January 1, 2016, and December 31, 2016. A diagnosis of UTI was categorized as cystitis, urethritis or pyelonephritis and was defined using the following ICD-10 codes: N30.0, N30.00, N30.01, N30.9, N30.90, N30.91, N39.0, N34.1, N34.2, and N10. The following antibiotics were prescribed: aminoglycosides, sulfamethoxazole/trimethoprim (TMP-SMX), cephalosporins, fluoroquinolones, macrolides, penicillins, tetracyclines, or nitrofurantoin. Patients were categorized based on gender, age, location, insurance payer and UTI type. We used χ 2 and Cochran-Mantel-Haenszel testing. Analyses were performed in SAS version 9.4 software (SAS Institute, Cary, NC). Results: In total, 15, 580 patients were included in this study. Prescriptions for antibiotics by drug class differed significantly by gender ( P < .0001), age ( P < .0001), geographic region ( P < .0001), insurance payer ( P < .0001), and UTI type ( P < .0001). Cephalosporins were prescribed more often to women (32.48%, 4, 173 of 12, 846) than to men (26.26%, 718 of 2, 734), and fluoroquinolones were prescribed more often to men (53.88%, 1, 473 of 2, 734) than to women (47.91%, 6, 155 of 12, 846). Although cephalosporins were prescribed most frequently (42.58%, 557 of 1, 308) in northern Virginia, fluoroquinolones were prescribed the most in eastern Virginia (50.76%, 1677 of 3, 304). Patients with commercial health insurance, Medicaid, and Medicare were prescribed fluoroquinolones (39.31%, 1, 149 of 2, 923), cephalosporins (56.33%, 1, 326 of 2, 354), and fluoroquinolones (57.36%, 5, 910 of 10, 303) most frequently, respectively. Conclusions: Antibiotic prescribing trends for UTIs varied by gender, age, geographic region, payer status and UTI type in the state of Virginia. These data will inform future statewide antimicrobial stewardship efforts. Funding: None Disclosures: Michelle Doll reports a research grant from Molnlycke Healthcare.